A Retrospective Study on the Incidence of Periprosthetic Fractures Related to Total Hip Arthroplasty and Postoperative Complications During Hospitalization - Victor Niculescu, Delia Carmen Nistor-Cseppento, Sebastian Tirla, Brigitte Osser, Cristina Aur, Diana Mocuta, Gheorghe Ion Popescu,Radu Dan Necula (CLINICS AND PRACTICE, 2025)
Background/Objectives: Periprosthetic fractures (PFs) are serious complications that can occur after total hip arthroplasty (THA), particularly in elderly patients who often have multiple comorbidities and low bone density. The surgical treatment of PFs typically involves internal fixation or revision arthroplasty, depending on the fracture type categorized by the Vancouver classification. This study examines the annual incidence of PFs and the complications that arise during hospitalization, as well as the predictive role of age in the occurrence of these fractures and their associated complications. Methods: Based on a retrospective observational study conducted over three years (2021–2023) at the Bihor County Emergency Hospital in Oradea, we analyzed 783 patients who underwent various hip surgeries. Results: The retrospective analysis identified 38 cases of PF out of 768 hip surgeries, resulting in an incidence of PF of 4.5%. Most PFs were classified as Vancouver B, with surgeries mainly involving internal fixation. Complications occurred in 23.68% of cases, including a mortality rate of 7.90%. A correlation analysis examining the relationship between age and post-surgical complications demonstrates a weak and statistically insignificant association (r = 0.120, p = 0.478). To highlight whether age is a predictive factor for PFs, we used the linear regression model; this suggests that older age explains 2.7% of the total variability in the incidence of PFs, being statistically significant ([F(1, 766) = 20.923], p < 0.001). Conclusions: The rising incidence of periprosthetic fractures is closely linked to the increasing number of total hip arthroplasties and the aging population. Fractures of this type are more common in elderly women, with no statistically significant differences have been found between the sexes.
Keywords: periprosthetic fractures; incidence; associated complication; age; predictor